Peptides of amaranth were targeted as containing sequences with potential anti-inflammatory properties - Moronta, Julián (2016)
The immunomodulatory effect of amaranth peptides on epithelial cells activated through the NF-κB signalling pathway was examined. Results showed that extensive protein hydrolysis from amaranth (23 and 30% degree of hydrolysis) reduced the emission of light in bacterial flagellin-activated Caco-2 CCL20: luc cells (Caco-2 cells transfected with a luciferase reporter under the control of the CCL20 promoter) compared with the non-hydrolysed protein. Purification of the most active peptide fractions by HPLC chromatography and sequencing showed that the peptide SSEDIKE possessed a modulatory capacity on activated cells to suppress the expression of mRNA coding for CCL20. This peptide was non-toxic for cells. These findings indicated that the peptide SSEDIKE derived from proteins of amaranth attenuated the activation of human intestinal epithelial cell, and hence amaranth proteins could be included in functional foods as a source of bioactive peptides with health promoting properties.